The nexus between asymmetric financial inclusion and economic growth: Evidence from the top 10 financially inclusive economies - Zhong Chen; Sajid Ali; Majid Lateef; Ahmad Imran Khan; Muhammad Khalid Anser (Borsa Istanbul Review, 2023)
Financial inclusion is an important component of financial development because it provides low-cost financial services to people and, hence, fosters economic growth. This research assesses the asymmetric relation between financial inclusion and economic growth in the top ten financially inclusive countries. Previous research employs panel data approaches, yielding standard results on the link between financial inclusion and economic growth, even though not all economies indicate such a correlation individually. The current study, by contrast, employs a unique approach, quantile-on-quantile, which allows us to explore time-series dependency in each country independently to produce worldwide yet nation-specific knowledge about the interaction between the variables. The results suggest that financial inclusion boosts economic growth at different quantiles in all countries. Furthermore, the degree of asymmetry in the variables varies by country, highlighting the need for governments to pay close attention when they adopt financial inclusion and economic growth policies.